Effects of climate change and anthropogenic pressures in the water quality of a coastal lagoon (Ria Formosa, Portugal) - Rodrigues, Marta (2021)
Understanding how climatic and anthropogenic drivers will influence coastal lagoons is fundamental to guarantee their preservation and sustainability. The Ria Formosa (coastal lagoon, South coast of Portugal) is a very important ecosystem that supports diverse economic activities in the region. The 3D coupled hydrodynamic-biogeochemical model SCHISM was validated and used to assess the influence of climate change and anthropogenic pressures on the water quality of the Ria Formosa. Five scenarios were simulated: reference scenario (S0), mean sea level rise (SLR) of 0.5 m (S1), increase of the air temperature of 1.68 °C (S2), increase of the outflow from the wastewater treatment plants (WWTP) by 50% (S3) and a combined scenario (S4). Results suggest that SLR of 0.5 m promotes an increase of 0.5-3 in the salinity near the area of influence of the WWTP. SLR decreases the inorganic nutrient concentrations in these areas by about 40-60%, due to an increase of the dilution. In contrast, the increase of the outflow from the WWTP by 50% increases the nutrients concentrations by about 20-40%. The increase of the air temperature alone by 1.68 °C increases the water temperature by 0-1 °C. The combined scenario suggests antagonist effects in the nutrient concentrations. Overall, the trophic index (TRIX) of the lagoon calculated for the scenarios exhibits only minor differences relative to the reference scenario, except in some areas near the WWTP discharges. In these areas, TRIX tends to increase with the increase of the outflow from the WWTP in scenario S3. These results provide further insight into the response of coastal lagoons, and the Ria Formosa in particular, to future changes and contribute to support their management.